THE ASSOCIATION BETWEEN STABLE CHRONIC ISCHEMIC HEART DISEASE, ATRIAL FIBRILLATION AND ARTERIAL HYPERTENSION AND THE SEVERITY OF COGNITIVE IMPAIRMENT AFTER FIRST EVER ISCHEMIC STROKE - Valkova M.; Veleva I.; Atanasova G.; Burgov R.; Guerguelcheva V.; Kostadinova P. (Science & Research)

(untitled)
Introduction: Post-stroke cognitive impairment (PCI) is associated with poor outcome and low quality of life. Stroke is associated with high level of vascular and heart pathology. The aim of our study was to examine the impact of stable chronic ischemic heart disease (CIHD), atrial fibrillation (AF) and arterial hypertension (AH) on PCI. Material and methods: We examined 109 patients (67males and 42 females) at first three days and at 90th day after the first ever ischemic stroke (with average result on National health stroke scale 12.23±2.50 points) via Mini Mental State Examination (MMSE), 10words Luria test for verbal memory (working memory and delayed recall at 30th minute), Isaack Set Test (IST) and Benton visual retention test (BVRT, variant A, E). 45 of them were with CIHD, 89 with AH and 18 AF. All results were interpreted at 95% confidential level. Results: The AH and AF had no significant influences on our tests, although the low arterial pressure was associated with poor MMSE test results at 90th day (p=0.0348). Patients with CIHD showed lower MMSE test results at 90th day than those without (р=0.0149), lower first and 90th day verbal working memory (p=0.0316, p= р=0.0074) and delayed recall (p= р=0.0118), lower points on 1st day IST (р=0.0122) and 90th day IST (р=0.0165) and more errors on 90th day BVRT (р=0.0177). Conclusions: CIHD is associated with memory and processing speed worsening after stroke. Not AH, but maintaining low blood pressure is related to poor global cognitive performance. AF has no additional impact on PCI.